SdiA Improves the Acid Tolerance of E. coli by Regulating GadW and GadY Expression - Ma, Xingyan; Zhang, Shebin; Xu, Zhenjie; Li, Honglin; Xiao, Qian; Qiu, Feng; Zhang, Weizheng; Long, Yifei; Zheng, Dexiang; Huang, Bin; Chen, Cha; Lu, Yang (Frontiers in Microbiology, 2020)
The acid tolerance mechanism is important for E. coli to resist acidic conditions encountered in mammalian host intestinal tract environment. Here, we explored how the LuxR protein SdiA influences E. coli acid tolerance ability in the context of the glutamate- and glutamine-dependent acid resistance system (AR2). First, using a growth and acid shock assay under different acid stress, we demonstrated that deletion of sdiA in SM10λπ or BW25113 lead to impaired growth under the acidic environment of PH 3-6, which was restored by complementary expression of SdiA. Next, transcriptome sequencing and qPCR disclosed that the expression of GadW and GadY, the key members of AR2, were regulated by SdiA. Further β-galactosidase reporter assays showed that the promoter activity of gadW and gadY was positively regulated by SdiA. Moreover, qPCR and β-galactosidase reporter assays confirmed that the regulation of SdiA on GadW but not GadY could be enhanced by quorum sensing signal molecules AHLs. Collectively, these data suggest that SdiA plays a crucial role in acid tolerance regulation of E. coli. Our findings provide new insight into an important contribution of quorum sensing system AHLs-SdiA to the networks that regulate acid tolerance.